2016
DOI: 10.1177/1756285616681943
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among COX-2, GPIIIa and P2Y1 variants are associated with aspirin responsiveness and adverse events in patients with ischemic stroke

Abstract: Background:The effect of gene variants and their interactions on response to aspirin and clinical adverse outcomes after an acute ischemic stroke (IS) is not fully understood. The aim of this study was to investigate the association of aspirin-relevant gene variants and their interactions with clinical adverse outcomes in IS patients taking aspirin.Methods:A total of 14 variants from six genes encoding COX enzymes (COX-1, COX-2), platelet membrane receptors (TXAS1, P2Y1, P2Y12) and glycoprotein receptor (GPIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Platelet aggregation was measured by light transmittance aggregometry (LTA). The procedure and the consistency were assessed according to our previous studies [ 17 20 ]. In brief, the platelet aggregation test was performed using a BioData PAPS-4 platelet aggregometer (Helena Laboratories).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet aggregation was measured by light transmittance aggregometry (LTA). The procedure and the consistency were assessed according to our previous studies [ 17 20 ]. In brief, the platelet aggregation test was performed using a BioData PAPS-4 platelet aggregometer (Helena Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on antiplatelet drug responsiveness have focused on evaluating stroke recurrence following IS, very limited studies have examined the relationship between antiplatelet drug resistance and END after acute IS. Our previous studies have shown that aspirin resistance is not only associated with RIS [ 19 , 20 ], but also associated with END after acute IS [ 5 , 21 ]. The association between CR and END following IS has not been specifically addressed, although our previous studies have shown CR is associated with RIS [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…COX and platelet receptors or glycoprotein receptor are involved in platelet activation, and are inhibited by aspirin. Although accumulating evidences have suggested that aspirin-relevant genetic variants may affect aspirin responsiveness and clinical adverse outcomes in IS patients [ 10 , 26 ], the CYP2C19 is not involved in action of aspirin and thus do not affect aspirin responsiveness and clinical adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation was associated the pathophysiology of atherogenesis and IS [ 15 , 16 , 18 , 19 ]. Our previous studies have administrated that the variants of platelet activation-relevant genes ( TXA2R, GPIIIa, P2Y12, P2Y1, TXAS1 ) not only increase the risk for IS, but also are associated with response to antiplatelet drugs and clinical adverse outcomes after IS [ 13 , 22 , 25 , 27 , 28 ]. However, the associations of the variants in platelet activation-relevant genes with carotid plaque vulnerability were not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that genes contribute to the complex diseases only by interactions with other genes, and the effects of individual variant may be too small to be detected [ 30 ]. Our previous studies have administrated that the GMDR analysis may be helpful to understand complex genetic etiology of IS [ 22 , 25 , 27 , 28 ]. However, few studies used the GMDR approach to investigate complex genetic risk for carotid plaque vulnerability.…”
Section: Discussionmentioning
confidence: 99%